“It is really so exhausting”: Exploring intensive care nurses’ perceptions of 24-hour long shifts - Virya Koy (2020)
© 2020 John Wiley & Sons Ltd Aim and objectives: To explore the perceptions and experiences of Cambodian ICU registered nurses regarding their working 24-hr shifts. Background: In Europe and the USA, nurses are moving to a 12-hr shift, and numerous studies have revealed the positive and negative effects of these. However, lesser known is the impact of 24-hr nursing shifts on care quality, and health and safety. In Cambodia, 100% of nurses are rostered for these in their shift patterns, but until this study no research had been conducted on such shifts. Design: A qualitative descriptive study. Method: Three focus group discussions were conducted with 30 registered nurses in July 2019, ten in each group, from three intensive care units of three hospitals in Cambodia. Data saturation was obtained. Data were analysed using content analysis, and the COREQ was applied for reporting this study. Findings: The ICU nurses’ perspectives revealed significant and unacceptable effects of working shifts of ~25-hr length, taking into account staff handover. Two major themes arose: It is so exhausting and Compromised hospital care. Alarmingly, participants worked on average 72 hr per week, were exhausted, and nursed between 6 and 10 critically ill patients per shift. Conclusion: To our knowledge this is the first study on nurses working 24-hr shifts, revealing unacceptable, high risks for the health and safety of nurses and patients, with nursing activities left undone, and a lack of quality care. Relevance to clinical practice: Improving nurse and patient health and safety, and quality of care requires hospital leaders to work with government and nursing organisations to develop better shift strategies. Resources need to be provided so that: nurses can work a maximum 12-hr shifts; the ratio of nurses to patients is improved; and nurses can have decent break times. This has major implications, for not only practice, but also management, administration, budgets and education.